A novel matrix based systematic approach for vulnerability assessment. Issue 1 (3rd November 2020) - Sabouhi, Hamed; Doroudi, Aref; Fotuhi-Firuzabad, Mahmud; Bashiri, Mahdi
Abstract : Purpose: This paper aims to propose a novel matrix-based systematic approach for vulnerability assessment. Design/methodology/approach: The proposed method consists of two major steps. First, the power network is modeled as a topological combination of edges (transmission lines, transformers, etc.) and nodes (buses, substations, etc.). The second step is to use an axiomatic design-based index for topology analysis. This index is based on the systematic counting of possible routes from the start (generators) to destination (loads), considering load importance, before and after a disruption. Findings: The effectiveness of the proposed method is demonstrated through an illustrative example and the Institute of Electrical and Electronics Engineers (IEEE) 14-bus power system. It was shown that the load's importance influences the results of the vulnerability analysis. The proposed method has some advantages over traditional graph theory such as an explicit description of multiple transmission nodes and assets with multiple conversion processes. Furthermore, it would help the power grid operators and asset investment managers to be better to assess the vulnerable components. Research limitations/implications: The proposed method can be used in planning, optimization, robustness and hardening of power systems. Originality/value: The paper presents a matrix-based systematic approach to evaluate and quantify the vulnerability of the power grid's components.